Proposals to Reform the Food Process and its Impacton Constitutional Law - Alvarado Farfán, Lucía (2016)
In the case of food in favor of a child and teenager, states in Article 93 1, that while parents have both the duty to provide food for their children, this obligation, in case of absence or ignorance of the whereabouts of the parents , Could be assumed by older siblings, grandparents, collateral relatives up to the third degree or other responsible of the child and adolescent, in that sense the strictly stated articles indicate that the members of the family understood this as those people united by emerging legal links a intersex relationship, procreation and kinship according to the statement by Dr. Alex Placido 2 , - are to be owed each other, but in the Peruvian reality, food processing is not meeting Its aims that the rule has established since in practice we find many problems to be effective collection among these we have the bureaucracy, speed, form and way of enforcing compliance with food obligation, in that sense in the present work are some proposal of change in the food process with the sole aim of being fulfilled by what is established by the constitutional norm and supranational standards.